The Influence of Communication Styles and Media of Islamic Religious Education Teachers on Students' Religious Attitudes - Wahyudi, Ahmad; Rosyad, Abdul; Azis, Abdul; Ningsih, Erlin Indaya (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Islamic religious education in schools plays an important role in instilling religious values through effective communication between teachers and students and using appropriate media. This study aims to analyze the influence of communication styles (verbal and non-verbal) and communication media (print and electronic) of Islamic Religious Education teachers on students' religious attitudes in schools. The approach used is an associative quantitative approach to explore the relationship between these variables. Data collection was conducted using a questionnaire with a Likert scale, selected to measure students' religious attitudes objectively. The research sample comprised 86 respondents, chosen through purposive sampling with specific criteria, such as students actively participating in lessons and at specific grade levels. The data obtained were analyzed using SPSS, involving validity and reliability tests, classical assumptions, and multiple linear regression (including t-test and F-test). The analysis results show that the teachers' communication style has a significant and positive effect on students' religious attitudes (Sig. 0.000). In contrast, the communication media shows a significant but negative effect (Sig. 0.004). Simultaneously, both variables significantly affect students' religious attitudes (F-test, Sig. 0.000). These findings indicate that although a good communication style can improve students' religious attitudes, inappropriate communication media may negatively affect those attitudes. Therefore, teachers need to choose the right communication style and media, considering the context and characteristics of the students, to support the optimal development of religious character.